Nitrogen deficiency in Arabidopsis affects galactolipid composition and gene expression and results in accumulation of fatty acid phytyl esters - Gaude, Nicole; Bréhélin, Claire; Tischendorf, Gilbert; Kessler, Félix; Dörmann, Peter (My University, 2007)
Nitrogen is an essential nutrient for plants because it represents a major constituent of numerous cellular compounds, including proteins, amino acids, nucleic acids and lipids. While N deprivation is known to have severe consequences for primary carbon metabolism, the effect on chloroplast lipid metabolism has not been analysed in higher plants. Nitrogen limitation in Arabidopsis led to a decrease in the chloroplast galactolipid monogalactosyldiacylglycerol (MGDG) and a concomitant increase in digalactosyldiacylglycerol (DGDG), which correlated with an elevated expression of the DGDG synthase genes DGD1 and DGD2. The amounts of triacylglycerol and free fatty acids increased during N deprivation. Furthermore, phytyl esters accumulated containing medium-chain fatty acids (12:0, 14:0) and a large amount of hexadecatrienoic acid (16:3). Fatty acid phytyl esters were localized to chloroplasts, in particular to thylakoids and plastoglobules. Different polyunsaturated acyl groups were found in phytyl esters accumulating in Arabidopsis lipid mutants and in other plants, including 16:3 and 18:3 species. Therefore N deficiency in higher plants results in a co-ordinated breakdown of galactolipids and chlorophyll with deposition of specific fatty acid phytyl esters in thylakoids and plastoglobules of chloroplasts.